'My skin is hard' - adult learners' resistance to racialization and racism. Issue 3 (2nd September 2021) - Ennser-Kananen, Johanna
ABSTRACT: This article analyzes experiences of racialization in stories of adult learners with refugee experience who attend a basic education program at a Finnish community college. Throughout a two-year ethnographic study, several students shared stories and thoughts on racialization and racism with the white researcher on site (the author). This article tells and theorizes their stories to gain a deeper understanding of the workings of everyday racialization and racism in a Finnish educational context. Theoretically, the article draws on a Critical Race Theory (CRT) framework, which recognizes the inherence of racialization and racism in society and underlines the importance and legitimacy of BIPOC's "experiential knowledge" (Solrzano, 1997, p. 7). Specifically, I use Yosso's (2005) framework of community cultural wealth to understand three interactions that address racialization and everyday racism. As I examine the data excerpts, I am guided by the questions, How do students experience racism and racialization? and Which capitals/knowledges do they display in their dealing with racism and racialization? Findings illustrate how racialization is understood and resisted in interaction, offer new research avenues for expanding Yosso's framework, and have implications for serving students from minoritized groups, particularly students of color.